2012
DOI: 10.1186/1471-2458-12-663
|View full text |Cite
|
Sign up to set email alerts
|

Perceived discrimination and depression among low-income Latina male-to-female transgender women

Abstract: BackgroundThis study examines exposure to perceived discrimination and its association with depression among low-income, Latina male-to-female transgender women as well as evaluates the impact of sexual partner violence and mistreatment on depression.MethodsA total of 220 Latina male-to-female transgender women who resided in Los Angeles, California, were recruited through community based organizations and referrals. Participants completed individual interviews using a structured questionnaire. Depressive symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
104
3
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(115 citation statements)
references
References 39 publications
6
104
3
2
Order By: Relevance
“…These findings are in line with previous research on the association between stigmatization and psychological health. 7,13,43 For example, previous studies found that discrimination was significantly associated with severe depression in a sample of low-income, Latina transgender women, 7 and stigmatization was positively associated with psychological distress in an online sample of 1093 transgender participants. 13 This growing body of research brings attention to the social factors that contribute to high prevalence of psychological distress in transgender populations.…”
Section: Stigma and Mental Health Among Transgender Womenmentioning
confidence: 99%
See 3 more Smart Citations
“…These findings are in line with previous research on the association between stigmatization and psychological health. 7,13,43 For example, previous studies found that discrimination was significantly associated with severe depression in a sample of low-income, Latina transgender women, 7 and stigmatization was positively associated with psychological distress in an online sample of 1093 transgender participants. 13 This growing body of research brings attention to the social factors that contribute to high prevalence of psychological distress in transgender populations.…”
Section: Stigma and Mental Health Among Transgender Womenmentioning
confidence: 99%
“…17 Studies have explored the risk and protective factors associated with mental health problems among transgender women. In studies of transgender women, depression was associated with level of education and a self-reported history of sexual partner violence 7 as well as exposure to both verbal and physical abuse. 11 A study including 515 transgendered individuals (392 MTF and 123 [female-to-male] FTM) revealed that histories of attempted suicide were higher among young, unemployed participants with a co-occurring history of alcohol or drug treatment.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have reported higher prevalence of psychological distress, including depressive symptoms, low self-esteem, and suicidal ideation in community samples of transgender women (MacCarthy, Reisner, Nunn, PerezBrumer, & Operario, 2015;Operario & Nemoto, 2010). Due to their gender identity or expression, transgender people experience high levels of gender-based social oppression, or transphobia, including everyday discrimination, family rejection, and hate crimes (Bazargan & Galvan, 2012;Bradford, Reisner, Honnold, & Xavier, 2012;Koken, Bimbi, & Parsons, 2009;Lombardi, Wilchins, Priesing, & Malouf, 2002;Nuttbrock et al, 2010). Scholars have proposed that adverse mental health outcomes in transgender populations are a result of this gender-specific social oppression (Bockting, Miner, Swinburne Romine, Hamilton, & Coleman, 2013;Goldblum et al, 2012;Haas et al, 2010;Nuttbrock et al, 2013;Reisner, Gamarel, Dunham, Hopwood, & Hwahng, 2013).…”
mentioning
confidence: 99%